Developer Linear Model to Determine Fitness Capacity in Screening, Coaching and Training Evaluation - Purwanto, Bambang (Kemenpora, 2014)
The examination of VO2 max was commonly used to discriminate fitness capacity under physical test. These test protocols were not easy to perform massively, particularly in Indonesia. We tried to investigate a novel method to discriminate fitness capacity which could perform simple, massively and suitable for Indonesian. Subject characteristics were collected under rest. Subjects were 15-25 years of age and grouped as weight and non weight bearing exercise. The multivariate analysis was used to find discriminator among those characteristic data. Age and resting heart rate discriminated non weight bearing fitness capacity in the following function, z= (0.246*age)+(0.72*resting heart rate)–9.057. Body weight and resting heart rate discriminated weight bearing fitness capacity in the following function, z= 9.182- (0.07*body weight)+(0.205*resting heart rate).